Collaborative Learning and Mini Research Assignments on The History of Islamic Educational Thought: The Impact of Students' Critical Thinking Ability - Amrullah, Amrullah; Mustofa, Muhammad; Fuhaidah, Ulya (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to determine the effect of collaborative learning models and mini research assignments on the critical thinking skills of Postgraduate Students of the Islamic Education Study Program (PAI) of the State Institute of Islamic Studies (IAIN) Curup. The research design used in this study was non-experimental. The sampling technique used was total sampling by taking the entire population as research respondents. The sample in this study was the first-semester Postgraduate students in Class A and B of IAIN Curup. They have taken the History of Islamic Educational Thinking Course in the Academic Year of 2021-2022. Based on the statistical analysis to determine the relationship between collaborative learning and critical thinking skills, the tobserved (9. 110) was more significant than the tcritical (2,056). Furthermore, the obtained tobserved (26,674) was more significant than the tcritical (2,056) to determine the relationship between mini research assignments and critical thinking skills. The analysis also shows that Fobserved (571.6) was more significant than Fcritical (3.34). Therefore can be concluded, there was an effect of collaborative learning, partially and simultaneously, on the critical thinking skills of IAIN Curup Postgraduate Students.